Construction Contracts Quality Assessment from the Point of View of Contractor and Customer - Arvydas Vilkonis; Jurgita Antucheviciene; Vladislavas Kutut (Buildings, 2023)
The cost and determination of construction projects are key issues for both customer and contractor when entering into a construction contract. For customers, calculation and evaluation of the cost of construction projects is complicated by the problem of underpricing, which may lead to the failure of contractors submitting a bid for a project, and, in addition, overpricing may lead to an overestimation of the average market value of specific groups of works. Therefore, the aim of the study is to compare the quality assurance of different contractors’ contracts using a multi-functional decision-making process and to develop a set of quality assessment criteria. The Analytic Hierarchy Process (AHP) was used to determine the significance of the criteria and afterwards to evaluate the construction contracts. Two groups of experts were involved in this research: specialists for the customer group, and specialists for the contractor group that comprised professionals in their respective fields, with many years of experience in managing and implementing construction projects. Based on the results of this study, conclusions and recommendations are presented regarding possibilities of ensuring quality of construction contracts and minimizing disputes between customer and contractor.